Understanding Customer Purchase Intention of PC Product on Indonesia - Manda Rahmat Husein Lubis; Nuryakin Nuryakin; Susanto Susanto (APMBA (Asia Pacific Management and Business Application), 2018)
In this digital revolution all industries are competing to innovate to attract consumers' attention. One of the most competitive competition is in the electronics industry. This study aims to determine the effect of brand awareness, brand image and perceived quality towards purchase intention of  IT products. The object in this research is  one of the leading lapotop brang in Indonesia in one of the growing provinces in Indonesia. This study uses sampling by purposive sampling technique. The number of samples in this study were 142 respondents. Data obtained through questionnaires distributed directly to the field and through the Google Form. Data analysis techniques using SEM showed that brand awareness has no significant effect on perceived quality, brand image has a significant effect on perceived quality, brand awareness has a significant effect on purchase intention, brand image has a significant effect on purchase intention and perceived quality have a significant effect on purchase intention. In generally, ASUS brand laptops have managed to attract consumers' attention through their brand image and awareness.